Application of the Green Marketing in Automotive Industry: Case Study of Slovak Republic - Margareta NADANYIOVA; Lubica GAJANOVA; Jana MAJEROVA (Communications of International Proceedings, 2020)
Recently, societal and global interest as well as the need and necessity of solving environmental problems are also reflected in marketing, namely by a gradual transition to the application of green marketing. If a company wants to be successful, competitive and ultimately popular with customers, it has to adapt to this trend. In this reason, many business managers in various industries see green marketing as a significant competitive advantage, investing in the future, or building a good image in the eyes of customers. Based on this, the article is aimed on the analysis of the green marketing in the automotive industry and its application in Slovak conditions. This includes providing the theoretical background and analysis of the green marketing from the viewpoint of Slovak and foreign authors. The important source for secondary data was scientific researches, annual company reports, statistical databases, published professional publications. Based on the analysis results, benefits of the green marketing are highlighted such as gaining competitive advantage, improving company's image, increasing customer's loyalty and brand value.
Keywords: Green Marketing; Automotive Industry; Corporate Social Responsibility; Sustainability.